Efektivitas Kompres Daun Kubis (Brasscis Oleracia Var Capitata) dan Breastcare Terhadap Pengurangan Pembengkakan Payudara Ibu Nifas di Bpm Ade Kismi Bania - Pititika Sarpari; Lili Farlikhatun (Malahayati Nursing Journal, 2024)
ABSTRACT Breast milk dams are a problem that often occurs at the beginning of the postpartum period, which can cause discomfort so that it becomes one of the obstacles in exclusive breastfeeding. Therefore, an effective method is needed to overcome this problem. Based on the results of a preliminary survey at BPM Ade Kismi Bania, out of 24 postpartum mothers, 17 postpartum mothers experienced breast swelling and 7 postpartum mothers did not experience breast swelling. Based on the above, the researcher is interested in conducting research entitled "Effectiveness of Cabbage Leaf Compresses (Brasscis Oleracia Var Capitata) and Breastcare on Reducing Breast Swelling in Postpartum Mothers at BPM Ade Kismi Bania". To determine the effectiveness of giving cold cabbage leaf compresses to the swelling scale and pain intensity in postpartum mothers with breast swelling. This study used a true experimental design with a pretest-posttest research design with a control group, with a total sample of 34 postpartum women with breast swelling divided into two groups (intervention-control). Data techniques are included in the analysis of research data using the Wilcoxon and Mann-Whitney tests using the SPSS program statistical calculations. The results of this study showed that cold cabbage leaf compresses had an effect on reducing the scale of swelling and pain intensity in the breast with a p-value of 0.002 (0.05), Breastcare also had a significant effect on the scale of swelling and pain intensity with p-value 0.05. There was a significant difference between the two groups in reducing the swelling scale and pain intensity (p-value 0.05). Giving cold cabbage leaf compresses has a significant difference in increasing the amount of breast milk when compared to giving breastcare treatment. It is hoped that the cold cabbage leaf compress method can be implemented in postpartum women who experience breast swelling. Keywords: Cabbage Leaf Compress, Breastcare, Swelling  ABSTRAK Bendungan ASI merupakan masalah yang sering terjadi pada awal ibu nifas, yang dapat menimbulkan ketidaknyamanan sehingga menjadi salah satu hambatan dalam pemberian ASI ekslusif. Oleh karena itu, diperlukan metode yang efektif dalam mengatasi masalah ini. Berdasarkan hasil survai pendahuluan di BPM Ade Kismi Bania dari 24 ibu nifas terdapat 17 ibu nifas mengalami pembengkakan payudara dan 7 ibu nifas tidak mengalami pembengkakan payudara. Berdasarkan hal tersebut diatas maka peneliti tertarik untuk melakukan penelitian yang berjudul “Efektivitas Kompres Daun Kubis (Brasscis Oleracia Var Capitata) Dan Breastcare Terhadap Pengurangan Pembengkakan Payudara Ibu Nifas Di BPM Ade Kismi Bania”. Mengetahui efektivitas pemberian kompres daun kubis dingin terhadap skala pembengkakan dan intensitas nyeri pada ibu Nifas dengan pembengkakan payudara. Penelitian ini menggunakan true experimental design dengan design penelitian pretest-posttest with control group, dengan jumlah sampel 34 ibu nifas dengan pembengkakan payudara yang dibagi kedalam dua kelompok (intervensi-kontrol). Teknik data termasuk dalam analisis data penelitian menggunakan uji Wilcoxon dan Mann-Whitney menggunakan perhitungan statistik program SPSS. Hasil dari penelitian ini menunjukkan kompres daun kubis dingin memiliki pengaruh terhadap penurunan skala pembengkakan dan intensitas nyeri pada payudara dengan p-value masing-masing 0,002 (0,05), Breastcare juga memiliki pengaruh bermakna terhadap skala pembengkakan dan intensitas nyeri dengan p-value 0,05. Terdapat perbedaan yang signifikan pada kedua kelompok dalam menurunkan skala pembengkakan dan intensitas nyeri (p – value 0,05). Pemberian kompres daun kubis digin memiliki perbedaan signifikan dalam meningkatkan jumlah ASI bila dibandingakn dengan pemberian perlakuan breastcare. Diharapakan metode kompres daun kubis dingin dapat dimplementasian pada ibu nifas yang mengalami pembengkakan payudara. Kata Kunci: Kompres Daun Kubis, Breastcare, Pembengkakan